Pengaruh Temperatur Pirolisis terhadap Kinetik Rate dan Volume Tar pada Limbah Serbuk Kayu Mahoni - Purbo Suwandono; Andy Hardianto (Universitas Muhammadiyah Sidoarjo, 2019)
Pyrolysis is an alternative technology that is a method for obtaining hydrocarbon energy sources. This technology is a combustion technology without involving O2 in the combustion process. The source of fuel from pyrolysis comes from renewable resources such as biomass / plants. Wood powder itself can be obtained from wood waste around us, so wood powder which is a biomass can also be used as raw material in the pyrolysis process. So far wood waste has only been used as a medium for planting mushrooms and fires. Whereas the use of wood waste in the manufacture of liquid smoke and charcoal has received attention in recent years, which can be produced by the pyrolysis method. The hypothesis of the study is that the higher the temperature, the higher the kinetic rate and volume of tar. this is because the energy given to biomass is also higher. The research method is to pyrolyze the material into the pyrolyzer machine with temperature variations, and later the reaction rate kinetic of the formed tar will be calculated. From this study we can conclude a number of things, namely: The higher the temperature of the volume of tar produced will be more numerous where the maximum volume obtained at a temperature of 500oC is 72 ml, but at very high temperatures the tar volume decreases because a lot of gas is formed. The higher the heating temperature, the kinetic rate that occurs in the decomposition of mahogany wood will also be faster, this has been validated the accuracy of the kinetic rate that occurs by comparing the actual volume with the volume of calculation results. The higher the heating temperature, the activation energy (Ea) and the exponential factor (A) will be smaller.